Utilization of Zakat Funds in Improving Human Development: A Study on Scholarship Recipients of DKI Jakarta National Amil Zakat Agency - Nur Athifah Lubis, Aisyah; Faizi, Faizi (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2024)
this study aims to evaluate the effectiveness of zakat funds in improving human development through the Future of Jakarta Scholarship (FJS) programme, which addresses important issues such as the sub-optimal allocation of zakat in education, high dropout rate, and inadequate level of human development. Using descriptive qualitative research method, this study collected primary data through interviews. Interview subjects include zakat recipients, programme administrators, education experts and community leaders, to provide a comprehensive understanding of the impact of the programme. The FJS theoretical framework combines zakat and Islamic finance theories, highlighting the role of zakat in socio-economic development and poverty alleviation, alongside human development theory to assess its impact on life expectancy, years of schooling, and purchasing power. The findings show that the FJS programme effectively meets criteria such as accuracy, awareness, purpose, and monitoring in distributing zakat funds. This positive impact is seen from the increase in life expectancy, increase in years of schooling, and increase in purchasing power among the beneficiaries.